Perancangan Analisis Risiko untuk Memenuhi ISO 45001:2018 Klausul 6 di Universitas X - Rianty Oshin Allo Bunga’; I Nyoman Sutapa (Jurnal Titra, 2022)
The international standard ISO 45001:2018 is a standard that needs to be applied for organizations in ensuring the welfare of workers. X University as an organization that is participating in expanding its scope internationally, both through internal and external activities, also requires an international standard in ensuring the safety and health of the entire community in it. Research was conducted to design ISO 45001:2018 at X University, especially in clause 6 that design by identifying hazards, assessing, and proposing controls. The research was conducted by conducting qualitative observations and interviews on 10 X University activities. The results of the analysis show that campus maintenance has the most high risk activities, the most dangerous causes are due to worker negligence, the most dangerous impact is serious injury, and the most proposed control is administrative.